A proportionate, universal parenting programme to enhance social-emotional well-being in infants and toddlers in England: the E-SEE Steps RCT - Tracey Bywater; Vashti Berry; Sarah Blower; Matthew Bursnall; Edward Cox; Amanda Mason-Jones; Sinéad McGilloway; Kirsty McKendrick; Siobhan Mitchell; Kate Pickett; Gerry Richardson; Kiera Solaiman; et al. (NIHR Journals Library, 2022)
Background: Mental disorders have become a public health crisis. Early prevention is key. Parenting programmes are effective for children aged ≥ 3 years; however, there is a lack of evidence of their effectiveness for children aged ≤ 2 years. Objectives: To establish if the model named Enhancing Social-Emotional Health and Well-being in the Early Years (E-SEE) Steps can (1) enhance child social emotional well-being and establish whether or not it is cost-effective at 20 months of age when compared with services as usual; and (2) be delivered as a proportionate universal model with fidelity. Design: A pragmatic two-arm randomised controlled trial and economic appraisal, with an embedded process evaluation to examine the outcomes, implementation and cost-effectiveness of the intervention, and intervention uptake, compared with services as usual. The study had an external pilot phase (which was originally planned as an internal pilot). Setting: The intervention was delivered in community settings by early years children's services and/or public health staff in four sites. Participants: A total of 341 parents of infants aged ≤ 8 weeks were randomised in a ratio of 5 : 1 (intervention, n = 285; control, n = 56). The target sample was 606 parents. Intervention: Two Incredible Years® parenting programmes (i.e. infant and toddler) delivered in a proportionate universal model with three levels [one universal (book) and two targeted group-based parenting programmes]. Main outcome measures: Child social and emotional well-being (primary outcome) was assessed using the Ages and Stages Questionnaire: Social and Emotional, 2nd edition, at 2, 9 and 18 months after randomisation. Parent depression (secondary key outcome) was assessed using the Patient Health Questionnaire-9 items. Both questionnaires were eligibility screeners for targeted groups. Results: The primary outcome analysis provided no evidence that the E-SEE Steps model was effective in enhancing child social and emotional well-being. The adjusted mean difference was 3.02 on the original Ages and Stages Questionnaire: Social and Emotional, 2nd edition, in favour of the control [95% confidence interval -0.03 to 6.08; p = 0.052; N = 321 (intervention, n = 268; control, n = 53)]. Analysis of the key secondary outcome (i.e. parent depression levels as assessed by the Patient Health Questionnaire-9 items) provided weak evidence on the Patient Health Questionnaire-9 items in favour of the intervention (adjusted mean difference -0.61, 95% confidence interval -1.34 to 0.12; p = 0.1). Other secondary outcomes did not differ between arms. The economic analysis showed that the E-SEE Steps model was associated with higher costs and was marginally more effective (0.031 quality-adjusted life-years gained from E-SEE Steps compared with SAU, 95% confidence interval -0.008 to 0.071) than services as usual, resulting in an incremental cost-effectiveness ratio of approximately £20,062 per quality-adjusted life-year compared with services as usual. Overall take-up of the targeted parenting programmes was low. Sites, although enthusiastic, identified barriers to delivering the intervention. Limitations: The target sample size was not met and the study was not powered to explore the effectiveness of each level of intervention. Most parents in the sample were well educated and, therefore, the results are unlikely to be generalisable, particularly to those at greatest risk of poor social and emotional well-being. Conclusions: The E-SEE Steps proportionate universal model did not enhance child social and emotional well-being, but generated non-significant improvements in parent health outcomes, resulting in considerable uncertainty around the cost-effectiveness of the intervention. The primary and key secondary outcome gave inconsistent signals. Although, with system changes, increased resources and adaptations to the intervention, the model could be implemented, evidence for positive outcomes from the E-SEE Steps model is poor. Future work: The universal-level E-SEE Step data (i.e. the Incredible Years book) from the external pilot will be pooled with the main trial data for further exploration up to follow-up 1, which is the time point at which most change was seen. Trial registration: This trial is registered as ISRCTN11079129. Funding: This project was funded by the National Institute for Health and Care Research (NIHR) Public Health Research programme and will be published in full in Public Health Research; Vol. 10, No. 8. See the NIHR Journals Library website for further project information.